ADAPTATION AS INTER-SEMIOTIC TRANSLATION: A STUDY FOCUSING ON THE VISUAL TEXT KALIYATTOM, AN ADAPTATION OF OTHELLO - JYOTSNA KRISHNAN (BEST: International Journal of Humanities, Arts, Medicine and Sciences (BEST: IJHAMS), 2015)
The concept of Intersemiotic Translation exposes a current and relevant area of discipline. It is a major focus of literary and film studies which couples these two relevant disciplines. The paper discusses how film adaptation becomes a mode of inter semiotic translation focussing on Kaliyattom, an adaptation of Othello, a Shakespearean play. Film adaptations took idea of the different aspect form the then existing literary adaptations. It has been a point of discussion when it becomes a cross cultural communication. The story written in a context is re written in another and it can be called as inter semiotic translation. Various aspects of Kaliyaattom like theme, plot, medium, narration, symbols are analysed in the paper.